1999
DOI: 10.1046/j.1365-2257.1999.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble transferrin receptor and the prediction of marrow aspirate iron results in a heterogeneous group of patients

Abstract: Serum soluble transferrin receptor (sTfR) concentration has been evaluated in the diagnosis of iron deficiency in otherwise healthy individuals and in patients with rheumatoid arthritis, but has not been studied in a general population of patients with complicated clinical presentations. In this study, 145 anaemic patients with a variety of medical conditions undergoing diagnostic bone marrow aspiration for any reason were tested by a complete blood count, a panel of biochemical tests to evaluate iron status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 21 publications
4
36
0
3
Order By: Relevance
“…The results of research conducted by other authors confirm the usefulness of an assessment of soluble transferrin receptor in diagnosing iron deficiencies [18][19][20][21]. Those authors recommend sTfR as a reliable index which makes it possible to assess the assimilability of iron during the treatment of its systemic deficiencies [19].…”
Section: Fig 2 Diagram Proposed For Assessing the Risk Of Anemia Insupporting
confidence: 65%
See 1 more Smart Citation
“…The results of research conducted by other authors confirm the usefulness of an assessment of soluble transferrin receptor in diagnosing iron deficiencies [18][19][20][21]. Those authors recommend sTfR as a reliable index which makes it possible to assess the assimilability of iron during the treatment of its systemic deficiencies [19].…”
Section: Fig 2 Diagram Proposed For Assessing the Risk Of Anemia Insupporting
confidence: 65%
“…Those authors recommend sTfR as a reliable index which makes it possible to assess the assimilability of iron during the treatment of its systemic deficiencies [19]. The usefulness of sTfR assessment in the identification of anemia type was confirmed by, among others, Tarng and Huang.…”
Section: Fig 2 Diagram Proposed For Assessing the Risk Of Anemia Inmentioning
confidence: 70%
“…In a heterogeneous group of anemic patients, the sensitivity and speci®city were, respectively, 71% and 74% for sTfR and 25% and 99% for serum ferritin with respect to diagnosis of absence of stainable iron in bone marrow [9]. To explain the relatively poor performance of the sTfR assay, Means et al postulated that in iron de®ciency, tissue iron stores can become depleted while iron supply from the circulation is still adequate to sustain near-normal erythropoiesis [9]. Therefore, synthesis of cellular TfR levels may still be relatively normal and the sTfR level may not increase but still be lower then expected in view of the low tissue iron stores and the correspondingly low ferritin levels.…”
Section: Discussionmentioning
confidence: 97%
“…Additional authors found that sTfR was not superior to serum ferritin for the routine clinical evaluation of patients with IDA versus ACD [17,19]. In a heterogeneous group of anemic patients, the sensitivity and speci®city were, respectively, 71% and 74% for sTfR and 25% and 99% for serum ferritin with respect to diagnosis of absence of stainable iron in bone marrow [9]. To explain the relatively poor performance of the sTfR assay, Means et al postulated that in iron de®ciency, tissue iron stores can become depleted while iron supply from the circulation is still adequate to sustain near-normal erythropoiesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…In unselected populations of patients with a variety of diagnoses, the specificity and positive predictive value of an elevated sTfR level for the diagnosis of iron deficiency is low because many patients have other reasons (predominantly increased erythropoiesis) for it [65]. Combining sTfR and ferritin measurements may increase specificity but not sensitivity for the diagnosis of iron deficiency in such a population [108].…”
Section: Soluble Tfr: a Marker Of Iron Status And/or Erythropoiesis?mentioning
confidence: 99%